MASSIF‐1: a beamline dedicated to the fully automatic characterization and data collection from crystals of biological macromolecules. (4th October 2015) - Bowler, Matthew W.; Nurizzo, Didier; Barrett, Ray; Beteva, Antonia; Bodin, Marjolaine; Caserotto, Hugo; Delagenière, Solange; Dobias, Fabian; Flot, David; Giraud, Thierry; Guichard, Nicolas; Guijarro, Mattias; et al.
Abstract : MASSIF‐1 (ID30A‐1) is an ESRF undulator beamline operating at a fixed wavelength of 0.969 Å (12.8 keV) that is dedicated to the completely automatic characterization of and data collection from crystals of biological macromolecules. The first of the ESRF Upgrade MASSIF beamlines to be commissioned, it has been open since September 2014, providing a unique automated data collection service to academic and industrial users. Here, the beamline characteristics and details of the new service are outlined.